Criticism of Peruvian literature and Mariateguian Marxism as a sociology of knowledge - García, Gonzalo F. (2023)
The Marxist approach attributes ideas and literary production to the level of development of material productive forces, that is, to the “economic structure” on which certain forms of “social consciousness” are erected. From there, the emphasis is placed on the interests that influence knowledge and on revealing the dominant ideology as a consequence of social class domination. The classic political economy, Hegel’s philosophy of law, and liberal thinking are explained in light of the rise of the middle class that had achieved political and economic power in Europe; a historical condition that could not simply be assumed in Latin America. Therefore, Mariateguian Marxism demands an effort of resignification to be able to characterize the fundamental aspects of the Peruvian socio-historical formation. It is therefore a remarkable effort in self-understanding one’s own social reality. Mostly, it is an innovative way to analyze and explain critically the phenomenon of literature that expresses the specific character of Latin American modernity, which suggest a different strategy of analysis than history of ideas and intellectuals.